Detection of Jingmenviruses in Japan with Evidence of Vertical Transmission in Ticks - Kobayashi, Daisuke; Kuwata, Ryusei; Kimura, Toshiya; Shimoda, Hiroshi; Fujita, Ryosuke; Faizah, Astri Nur; Kai, Izumi; Matsumura, Ryo; Kuroda, Yudai; Watanabe, Shumpei; Kuniyoshi, Sawako; Yamauchi, Takeo; et al. (Viruses, 2021)
Jingmen tick virus (JMTV) and the related jingmenvirus-termed Alongshan virus are recognized as globally emerging human pathogenic tick-borne viruses. These viruses have been detected in various mammals and invertebrates, although their natural transmission cycles remain unknown. JMTV and a novel jingmenvirus, tentatively named Takachi virus (TAKV), have now been identified during a surveillance of tick-borne viruses in Japan. JMTV was shown to be distributed across extensive areas of Japan and has been detected repeatedly at the same collection sites over several years, suggesting viral circulation in natural transmission cycles in these areas. Interestingly, these jingmenviruses may exist in a host tick species-specific manner. Vertical transmission of the virus in host ticks in nature was also indicated by the presence of JMTV in unfed host-questing Amblyomma testudinarium larvae. Further epidemiological surveillance and etiological studies are necessary to assess the status and risk of jingmenvirus infection in Japan.